An Investigation of Sintering Parameters on Titanium Powder for Electron Beam Melting Processing Optimization - Drescher, Philipp (Materials (Basel), 2016)
Selective electron beam melting (SEBM) is a relatively new additive manufacturing technology for metallic materials. Specific to this technology is the sintering of the metal powder prior to the melting process. The sintering process has disadvantages for post-processing. The post-processing of parts produced by SEBM typically involves the removal of semi-sintered powder through the use of a powder blasting system. Furthermore, the sintering of large areas before melting decreases productivity. Current investigations are aimed at improving the sintering process in order to achieve better productivity, geometric accuracy, and resolution. In this study, the focus lies on the modification of the sintering process. In order to investigate and improve the sintering process, highly porous titanium test specimens with various scan speeds were built. The aim of this study was to decrease build time with comparable mechanical properties of the components and to remove the residual powder more easily after a build. By only sintering the area in which the melt pool for the components is created, an average productivity improvement of approx. 20% was achieved. Tensile tests were carried out, and the measured mechanical properties show comparatively or slightly improved values compared with the reference.